On the petrology and microstructures of small-scale ductile shear zones in granitoid rocks: An overview. (August 2022) - Ceccato, Alberto; Goncalves, Philippe; Menegon, Luca
Abstract: Since the pioneering works of John Ramsay in the 1970's and 1980's, the analysis of exceptional exposures of small-scale shear zones (i.e. 10 -3 – 10 −1  m thick) in granitoid rocks provided invaluable insights into the processes controlling strain localisation in the middle and lower continental crust. Indeed, recent advancement in field, microstructural and petrological analyses of such small-scale shear zone have shed new light on the metamorphic, tectonic and fluid conditions promoting shear zone nucleation and development in granitoid rocks. In this paper we provide an overview of these new insights, comparing and integrating the results obtained from field, and microstructural and petrological analyses of small-scale shear zones in granitoid plutons and meta-granitoids from the Alps. A review of the deformation temperature shows that the granitoid shear zones development occurs between 350 and 600 °C, with most of them localising in a restricted temperature window between 450 and 500 °C. At these conditions, the magmatic assemblage is metastable and subjected to a series of metamorphic reactions. Furthermore, the development of shear zone does not occur under-closed system conditions. Introducing or expelling fluids and mass (i.e. metasomatism) during deformation has mineralogical consequences that control the rheology and the way shear zone evolves. Among the main mineralogical and microstructural changes, the breakdown of magmatic feldspar(s) into fine-grained aggregates steers both the rheology and fabric evolution of shear zones in granitoid rocks, triggering further mechano-chemical feedback mechanisms. Future research should consider the occurrence of feedback processes between deformation, metamorphic and metasomatic processes to understand and quantify the evolution with time and strain of shear zone geometry and rheology, as well as of the development of larger-scale shear zone networks. Highlights: Small-scale shear zone are widespread features of meta-granitoid units and plutons. They develop at the transition between greenschist and amphibolite facies. A set of retrograde metamorphic reactions aid strain softening and localisation. Grain-size-sensitive and phase mixing processes steer shear zone rheology. Future research should aim at the quantification of deformation-fluids feedbacks.